2021
DOI: 10.3389/fevo.2021.694569
|View full text |Cite
|
Sign up to set email alerts
|

What Makes Spiders Frightening and Disgusting to People?

Abstract: The quality of human-animal interactions may crucially influence conservation efforts. Unfortunately, and despite their important roles in the functioning of the ecosystem, some animals are considered notoriously unpopular. Using the forced-choice paradigm, we investigated which cues humans perceive as frightening and disgusting in spiders, one of the most unpleasant animals in the world. The research was carried out with a representative sample of N = 1,015 Slovak adults. We found that perceived fear and disg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 58 publications
3
22
0
Order By: Relevance
“…1 ). This result is generally consistent with the study of Zvarikova et al 66 where the experimentally enlarged body parts of spider stimuli elicited greater fear.…”
Section: Discussionsupporting
confidence: 92%
“…1 ). This result is generally consistent with the study of Zvarikova et al 66 where the experimentally enlarged body parts of spider stimuli elicited greater fear.…”
Section: Discussionsupporting
confidence: 92%
“…All 3D assets employed in vBATon were created using Blender, a widely used free and open-source 3D computer graphics software (Community, 2018). In order to enhance the aversive nature of the spider displayed in vBATon, we utilized a model of a large wolf spider ( Lycosidae) with distinctive abdomen and chelicerae (Zvaríková et al, 2021). Previous research successfully demonstrated that animated spiders are able to elicit anxiety and disgust in spider-fearful individuals (Grill & Haberkamp, 2023b).…”
Section: Methodsmentioning
confidence: 99%
“…Examples of titles of sensationalistic versus non-sensationalistic news articles focusing on the same event are: “Thousands of spiders ‘bleed out of the walls’ and force family from home” vs. “Home Infested With Brown Recluse Spiders in Missouri”. Throughout the database, frequent words associated with sensationalistic content were ‘alarm’, ‘agony’, ‘attack’, ‘boom’, ‘deadly’, ‘creepy crawly’, ‘devil’, ‘fear’, ‘hell’, ‘killer’, ‘murderer’, ‘nasty’, ‘nightmare’, ‘panic’, ‘terrible’, ‘terrifying’, and ‘terror’ 2 , as well as magnifying adjectives that exaggerated any features of the encounter (e.g., body size 34 – 36 , hairiness 35 ). However, the presence of one of these words did not necessarily result in an article being scored as sensationalistic.…”
Section: Methodsmentioning
confidence: 99%